2018
DOI: 10.1097/md.0000000000011993
|View full text |Cite
|
Sign up to set email alerts
|

Tissue perfusion alterations correlate with mortality in patients admitted to the intensive care unit for acute pulmonary embolism

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Here, we found for the first time that increased index CRT and hyperlactatemia were associated with IHI occurrence, as well as impaired global hemodynamics defined by a cardiovascular SOFA score ≥1. More interestingly, we found a cumulative predictive effect of these parameters similar to that we observed in the setting of severe pulmonary embolism [49]. Combining them in a score which can be quickly and easily calculated at the bedside could be helpful to improve risk stratification.…”
Section: Discussionsupporting
confidence: 77%
“…Here, we found for the first time that increased index CRT and hyperlactatemia were associated with IHI occurrence, as well as impaired global hemodynamics defined by a cardiovascular SOFA score ≥1. More interestingly, we found a cumulative predictive effect of these parameters similar to that we observed in the setting of severe pulmonary embolism [49]. Combining them in a score which can be quickly and easily calculated at the bedside could be helpful to improve risk stratification.…”
Section: Discussionsupporting
confidence: 77%
“…After reviewing the full-text articles, 14 studies were removed due to no available data or overlapping the study population. Finally, 6 studies 13,1719 with 1706 patients were evaluated in our meta-analysis.
Figure 1.Flow chart of literature selection.
…”
Section: Resultsmentioning
confidence: 99%
“…Three of the included studies were prospective, the others were retrospective design. Lactate concentrations were obtained from venous blood sampling in two studies, 20,21 while four studies 13,[17][18][19] evaluated arterial lactate levels. Five studies used 2 mmol/L as a cut-off value, while one study had a venous lactate cut-off value of 3.3 mmol/L.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Many laboratory and clinical prognostic markers and scores have been developed for APE, such as risk stratifications, pulmonary embolism severity index (PESI) score ( 10 ), clinical parameters such as hypotension, the ratio of the right ventricle diameter to the left ventricle diameter (RV/LV ratio), superior vena cava (SVC) diameter ( 11 ), and troponin ( 12 ), brain natriuretic peptide (BNP) ( 13 ), and lactate levels ( 14 ). Recently, a study by Gul et al ( 15 ) that investigated the correlation between the heart-type fatty acid-binding protein (H-FABP) and the clot burden score demonstrated that the H-FABP predicts 30-day mortality in APE and is a strong predictor of poor prognosis.…”
Section: Introductionmentioning
confidence: 99%